Avaliação biológica de compósitos de polímeros biodegradáveis em uma matriz de biocerâmica com adição de tetraciclina - Andre Luiz Pataro (2005)
Calcium phosphate bioceramics have been demonstrated a good alternative for bone replacing, due its intrinsic bioativity, despite some manipulation difficulties. A significant amount of scaffolds for tissue engineering are made from biodegradable polymers such as PLGA and PLA, known by its plasticity and degrability. Thus, this two kinds of biomaterias could have its proprieties optimized by forming composites. Additionaly, tetracycline (TCN) is well known for its large spectrum antibiotic, anti-inflamatory and other non-antimicrobial activities. The objective of the present work was to evaluate the biological response of composites of biodegradable polymers (PLA, PLGA) dispersed in a bioceramic matrix (Osteosynt® - BC) with tetracycline addition. It were performed direct contact test (ASTM F-813), eluation test (USP XXIII) and biocompatility test by macroscopic and microscopic analyses on outbread swiss mice 1, 7, 13, 21, 28 and 56 days after subcutaneus implantation. It was verified low citotoxicity in vitro of the composites PLA:BC and PLGA:BC when compared to the controls. It was observed a low to moderate inflammatory response for most of the groups. The tissue showed normal pattern after 21 days for all the groups. It could be noted angiogesesis and celular adsortion. TCN addition favorably interfered in the in vitro biological response. Macroscopic observations showed that the composites with PLGA degradated much faster than those with PLA, as same as the controls PLGA and PLA. In conclusion, the composites were biocompatible, promising possible application for bone tissue engineering.